Cooperative twinning behavior leads to superior mechanical properties in a coherently precipitated high-entropy alloy - Shuai Yuan; Xinghao Du; Dezheng liu; Chenxi Yuan; Zeyu Xing; Jinyu Zhang; Hechuan Ma; Shijun Zhao; Wanpeng Li; Baolin Wu; Jun Sun (Journal of Materials Research and Technology)
The mechanical properties of the coherently precipitated high-entropy alloys can be further enhanced by enhancing the strain hardening behavior through deformation twins. In this study, a heterogeneously structured Ni45Co21Fe15Cr10Al4·5Ti4.5 (at. %) alloy with micro-meter-sized grains embedded inside a matrix of nanocrystalline or ultrafine grains was obtained through tailored thermomechanical processing steps. The tested alloy exhibited favorable strain hardening behavior, resulting in a remarkable tensile ductility of 32% even under the high yield stress of 1400 MPa. Dense planar defects comprised of deformation twins (DTs) have been activated in the grains composed of γ phase and coherently precipitated γ′ phase during the tensile process at room temperature. The underlying mechanism for the nucleation and growth of DTs in the grains with γ/γ′ duplex phases has been elucidated through transmission electron microscopy observations and density functional theory calculation, emphasizing the importance of the DTs. This research provides new insights into designing high entropy alloys that overcome the trade-off between strength and ductility.